2022
DOI: 10.1128/msphere.00512-22
|View full text |Cite
|
Sign up to set email alerts
|

Species-Specific Patterns of Gut Metabolic Modules in Dutch Individuals with Different Dietary Habits

Abstract: Diet is an important modulator of the human gut microbiome, which is susceptible to increased consumption of plant fibers in vegan or vegetarian lifestyles. To investigate this, we compared the gut microbiome of Dutch adults following omnivorous, pescatarian, vegan and vegetarian diets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…However work continues to emerge that suggests that beyond calorie restriction, dietary composition, such as a plant based, high fiber, low fat diet, should be considered. What is most remarkable is how quickly the gut microbiome can be modulated to express a health promoting composition despite decades of consumption of an obesogenic, high alcohol consumption, diabetogenic high fat, low fiber western type diet [27][28][29][30].…”
Section: Diet the Microbiome And Anastomotic Leakmentioning
confidence: 99%
“…However work continues to emerge that suggests that beyond calorie restriction, dietary composition, such as a plant based, high fiber, low fat diet, should be considered. What is most remarkable is how quickly the gut microbiome can be modulated to express a health promoting composition despite decades of consumption of an obesogenic, high alcohol consumption, diabetogenic high fat, low fiber western type diet [27][28][29][30].…”
Section: Diet the Microbiome And Anastomotic Leakmentioning
confidence: 99%
“…Despite this, plant-based diets’ effects on the gut microbiome have been called attention to in the last decade because those diets have a high content of microbiota-accessible carbohydrates (MACs) that are not digested and absorbed by the host, such as resistant starch, inulin, xylan, and pectin. These compounds favour the growth of specialised taxa like Ruminococcus bromii , Roseburia intestinalis , and, especially, F. prausnitzii , which is associated with anti-inflammatory effects (Shetty et al, 2022; Sidhu et al, 2023; Trefflich et al, 2020). Also, high-fibre diets rich in MACs are reported to benefit host physiology via enhanced butyrate production and promote higher bacterial diversity (Shetty et al, 2022).…”
Section: Plant-based Dietsmentioning
confidence: 99%
“…These compounds favour the growth of specialised taxa like Ruminococcus bromii , Roseburia intestinalis , and, especially, F. prausnitzii , which is associated with anti-inflammatory effects (Shetty et al, 2022; Sidhu et al, 2023; Trefflich et al, 2020). Also, high-fibre diets rich in MACs are reported to benefit host physiology via enhanced butyrate production and promote higher bacterial diversity (Shetty et al, 2022). According to Losno et al (2021), the genus that is consistently reported as higher in vegans in contrast with omnivores is Prevotella.…”
Section: Plant-based Dietsmentioning
confidence: 99%
See 2 more Smart Citations